Seeing is believing: The evolving role of muscle ultrasound in comprehensive nutritional care of pediatric oncology patients—A case series - Corey Hawes; Vlad Călin Rădulescu; Senna Munnikhuysen (Nutrition in Clinical Practice, 2026)
Abstract Traditional nutritional assessments in pediatric oncology, such as weight and body mass index, often fail to accurately capture changes in body composition, frequently masking significant muscle depletion, or secondary sarcopenia. This retrospective case series evaluates the novel clinical application of muscle ultrasound (mUS) by a pediatric oncology dietitian to help objectively guide and monitor nutrition interventions. We report our observations regarding three pediatric patients with cancer (one school‐aged child and two adolescents/young adults). Serial mUS measurements of the quadriceps femoris and rectus femoris were obtained alongside standard anthropometric data. Nutritional interventions, including appetite stimulants and enteral nutrition, were tailored based on these combined assessments. In all three cases, mUS findings were discordant with total body weight trends. One patient exhibited weight gain on appetite stimulants, but mUS revealed concurrent muscle loss, prompting a transition to enteral nutrition. Conversely, another patient experienced persistent weight loss, but mUS confirmed muscle preservation and growth and led to reduced healthcare utilization. These observations suggest mUS is a feasible, non‐invasive tool with potential to complement conventional anthropometric measures by detecting subclinical muscle changes that may otherwise be missed. Given the small, heterogeneous sample and retrospective design, these findings should be considered as hypothesis‐generating rather than conclusive and warrant further validation in larger, prospective studies before mUS can be recommended as a standard component of nutritional assessment in pediatric oncology.